The Effectiveness Of Sikajari Media In Distance Learning For Elementary School Students - Chafid, Abdul; Santoso, Santoso; Widjanarko, Mochamad (Journal Prakarsa Paedagogia, 2022)
This study is a research and development of Sikajari-based distance learning media. This study aims to analyze the effectiveness of Sikajari media in distance learning with the sub-theme of Cultural Diversity of My Nation 4th grade elementary school students in the Jepara district. This development research adapts the Borg & Gall model which consists of (1) research and data collection, (2) planning, (3) development preliminary of product, (4) preliminary field testing, (5) main product revision, (6) main field test, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. Data collection techniques through pretest and posttest. Data analysis using the Gain score test. The results of the analysis showed that the average value of the pretest was 39.41 and the post-test was 84.88. The normalized gain value or n-Gain is 0.759 in the high category. This means that there is an increase in learning outcomes in the high category. The N-Gain % value is 75.9 which is interpreted in the effective category. That means the use of Sikajari media in distance learning is effective for improving learning outcomes of the Sub-theme of Cultural Diversity of my Nations for fourth-grade elementary school students in the Jepara Regency.